Consequences of Transplacental Transmission of the SARS-CoV-2 Virus: A Single-Center Experience - Ivona Djordjevic; Ana Kostic; Ivana Budic; Nikola Vacic; Zlatan Elek; Strahinja Konstantinovic (MDPI AG, 2022)
The issues of vertical viral transmission from mother to fetus and the potential complications caused by SARS-CoV-2 coagulopathy are still unclear. There are few literature data about the vertical transmission of SARS-CoV-2 and health outcomes in neonates born to mothers with symptomatic or asymptomatic coronavirus disease, with the existing data based on small sample sizes. This case series study consists of two newborn children (one pre-term and one term) who were born to SARS-CoV-2-positive mothers and admitted to the neonatal intensive care unit a few hours after birth. One child had cyanotic changes that affected the entire left leg and the left forearm, with multiple livid changes on the front of the chest and abdomen, the right upper arm, right thigh, neck, and face, and one child had an altered umbilical cord. The first child was treated conservatively, and the second child was treated surgically.